Rancang Bangun Alat Penghitung Jumlah Stok Barang Dagang Menggunakan Mikrokontroler Berbasis Web - Naaziat, Andi; Yuliatmojo, Pitoyo; Bintoro, Jusuf (JURNAL PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA (JVoTE), 2023)
This case study aims to design a stock counting device for merchandise that has a barcode and a digital code printed on the product packaging, which will later be scanned using the GM65 barcode sensor. The method used in this research is engineering, described through problem identification, tool and system design, from software to hardware. The system was tested through data analysis to obtain research results. Based on the results, it shows that the inventory counting system runs according to the initial design to determine the remaining items sold in the available stock in a supermarket. The resulting barcode is entered into a web server media with an internet network, so it is stored in a database. This is able to minimize confusion that occurs during stocktaking, and the data can be stored neatly and is not easily lost.